Dampak Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan dengan Struktur Kepemilikan serta Opini Audit sebagai Variabel Intervening pada Perusahaan Manufaktur Sub Sektor Semen yang Terdaftar di BEI - Dicky Satria Ananta Haqq; Hwihanus Hwihanus (Pajak dan Manajemen Keuangan, 2024)
This study examines the impact of capital structure and financial performance on the firm value of manufacturing companies in the cement sub-sector listed on the Indonesia Stock Exchange, with ownership structure and audit opinion as intervening variables. Utilizing a quantitative approach, the research analyzes secondary data from financial reports of cement companies for the period 2019–2023. A purposive sampling method was employed, yielding five eligible companies. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS software.The results indicate a significant effect of capital structure and financial performance on firm value, both directly and through the intervening variables. Ownership structure and audit opinion are proven to mediate the relationship between independent and dependent variables, providing valuable insights into the dynamics of firm value in the cement industry. These findings offer important implications for company management in optimizing capital, enhancing financial performance, and gaining investor trust to improve firm value.